2019
DOI: 10.3356/jrr-18-37
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Letter: Raptor Persecution

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Therefore, urban areas can provide suitable refugia for predators/raptors. Their presence, however, often trigger human-wildlife conflicts, specifically when livestock or pets are seen at risk (Redpath et al 2013;Madden et al 2019;Murgatroyd et al 2019;Reynolds et al in press).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, urban areas can provide suitable refugia for predators/raptors. Their presence, however, often trigger human-wildlife conflicts, specifically when livestock or pets are seen at risk (Redpath et al 2013;Madden et al 2019;Murgatroyd et al 2019;Reynolds et al in press).…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen percent of the world's bird species are threatened with extinction (IUCN 2020). Threats to avian populations include habitat loss (Harris and Pimm 2004), climate change (Liang et al 2018), overexploitation (Harris et al 2015, Panter et al 2019, persecution (Madden et al 2019), invasive species (Woinarski et al 2017) and the effects of anthropogenic activity such as energy production and use. One of the major impacts of energy production and use is electrocution of wildlife on power lines (Ferrer et al 1991, Bevanger 1998, Bayle 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, raptors have been involved in HWC [ 17 , 18 ], and persecution is stated as one of the major threats for these birds in many regions of the world [ 19 , 20 ]. To address these conflicts, certain studies evaluated the economic impacts produced by raptor predation on livestock and suggested that losses of domestic animals by raptor predation are usually exceptional and/or less than losses produced by other natural causes such as diseases [ 4 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%